2024
DOI: 10.3389/fnut.2024.1307701
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of antenatal micronutrients used as a treatment for maternal depression on infant temperament in the first year of life

S. A. Campbell,
S. P. Dys,
J. M. T. Henderson
et al.

Abstract: Antenatal depression and maternal nutrition can influence infant temperament. Although broad-spectrum-micronutrients (BSM: vitamins and minerals) given above Recommended Dietary Allowances during pregnancy can mitigate symptoms of antenatal depression, their associated effects on infant temperament are unknown. One hundred and fourteen New Zealand mother-infant dyads (45 infants exposed to BSM during pregnancy (range of exposure during pregnancy: 12–182 days) to treat antenatal depressive symptoms (measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Observational follow-up of the infants born to these mothers who took micronutrients antenatally showed positive effects on infant regulation, on par with or better than typical pregnancies and superior to antidepressants, 65 and no observed negative effects on temperament up to 1 year. 66 Blood tests suggested that increased micronutrient intake resulted in meaningful increases in vitamins B12 and D, with other research on this sample documenting that there were fewer women developing vitamin C deficiency for those in the micronutrient group compared with placebo. 67 The reduction in homocysteine in the micronutrient group provides insight into one potential mechanism of action in that the micronutrients may positively affect the methylation cycle, a cycle that supports the production of glutathione, an important antioxidant.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Observational follow-up of the infants born to these mothers who took micronutrients antenatally showed positive effects on infant regulation, on par with or better than typical pregnancies and superior to antidepressants, 65 and no observed negative effects on temperament up to 1 year. 66 Blood tests suggested that increased micronutrient intake resulted in meaningful increases in vitamins B12 and D, with other research on this sample documenting that there were fewer women developing vitamin C deficiency for those in the micronutrient group compared with placebo. 67 The reduction in homocysteine in the micronutrient group provides insight into one potential mechanism of action in that the micronutrients may positively affect the methylation cycle, a cycle that supports the production of glutathione, an important antioxidant.…”
Section: Discussionmentioning
confidence: 76%
“…However, replication with larger sample sizes, more severe pathology and more diverse population is imperative because of the preliminary nature of this study. The high placebo effect achieved with fewer side-effects than antidepressants and with positive infant outcomes 65,66 should be welcomed by patients and clinicians trying to navigate options during pregnancy, given the lack of controlled trials of antidepressants during the antenatal period. These findings align with the growing body of literature highlighting the potential advantage of an abundant nutritional environment in improving brain health.…”
Section: Discussionmentioning
confidence: 99%